Electron interaction with copper(II) carboxylate compounds - Lacko, Michal; Papp, Peter; Szymańska, Iwona B.; Szłyk, Edward; Matejčík, Štefan (Beilstein Journal of Nanotechnology, 2018)
In the present study we have performed electron collision experiments with copper carboxylate complexes: [Cu2(t-BuNH2)2(µ-O2CC2F5)4], [Cu2(s-BuNH2)2(µ-O2CC2F5)4], [Cu2(EtNH2)2(µ-O2CC2F5)4], and [Cu2(µ-O2CC2F5)4]. Mass spectrometry was used to identify the fragmentation pattern of the coordination compounds produced in crossed electron – molecular beam experiments and to measure the dependence of ion yields of positive and negative ions on the electron energy. The dissociation pattern of positive ions contains a sequential loss of both the carboxylate ligands and/or the amine ligands from the complexes. Moreover, the fragmentation of the ligands themselves is visible in the mass spectrum below m/z 140. For the studied complexes the metallated ions containing both ligands, e.g., Cu2(O2CC2F5)(RNH2)+, Cu2(O2CC2F5)3(RNH2)2+ confirm the evaporation of whole complex molecules. A significant production of Cu+ ion was observed only for [Cu2(µ-O2CC2F5)4], a weak yield was detected for [Cu2(EtNH2)2(µ-O2CC2F5)4] as well. The dissociative electron attachment processes leading to formation of negative ions are similar for all investigated molecules as the highest unoccupied molecular orbital of the studied complexes has Cu–N and Cu–O antibonding character. For all complexes, formation of the Cu2(O2CC2F5)4−• anion is observed together with mononuclear DEA fragments Cu(O2CC2F5)3−, Cu(O2CC2F5)2− and Cu(O2CC2F5)−•. All dominant DEA fragments of these complexes are formed through single particle resonant processes close to 0 eV.
Keywords: amines; dissociative electron attachment; dissociative ionization; FEBID; low energy electrons interaction